PERAN MEDIASI INSTITUSIONAL BUDAYA TERHADAP HUBUNGAN NILAI BUDAYA DAN PENGUNGKAPAN NILAI ISLAM - Violita, Evony Silvino; Syakhroza, Akhmad; Nasution, Mustafa Edwin (Jurnal Akuntansi dan Keuangan Indonesia, 2014)
This study aims to analyze mediation role of cultural institutional element on the influence of societal values on the disclosure of Islamic values. The cultural institutional elements analyzed are legal system, capital market development, and human development. This research covers 102 Islamic banks for the data of 2010 to 2012 around the world. The study finds that capital market development is the only element that has mediation role on the influence of culture on the disclosure of Islamic values. The capital market development has a partial mediation role on the influence of humane orientation on the disclosure of Islamic values and does not have mediation role on the influence of other cultural dimension (social orientation, power distance, and uncertainty avoidance). The capital market development has direct influence rather than mediation role on the disclosure of Islamic values. Meanwhile, the study cannot prove that the other two elements have mediation role in the influence of culture on the disclosure of Islamic values.